Comparison between a Bare–Metal Stents and Drug Eluting Stents in patients undergoing Percutaneous Coronary Intervention. - Khaled Alsayed (Al-Azhar University, Faculty of Medicine (Damietta), 2020)
Background: little researches have directly compared second-generation drug-eluting stents with each other or with bare-metal stents. Aim of the work: To compare between outcomes after implantation of bare-metal stents [BMS] and two kinds of 2nd generation drug eluting stents [DES] [Zotarolimus-Eluting Stents [ZES], and A Everolimus-Eluting Stents [EES]] in patients undergoing percutaneous coronary intervention. Patients and Methods: 160 Ischemic Heart Disease [IHD] patients undergoing PCI with 2nd generation DES implantation [80 ZES and 80 EES] were analyzed against 50 IHD patients undergoing PCI with BMS implantation. Each patients group received up to 6 [in BMS group] or 24 months [in ZES and EES groups] of clopidogrel therapy. The key efficacy endpoint was the 24 months major adverse cardiac event [MACE] [death, myocardial infarction, or target lesion revascularization], whereas stent thrombosis [ST] was the safety endpoint. Results: The MACE rate was lowest in EES [19%; χ2= 7.661], highest in BMS [41.7%; χ2 =7.661], and intermediate in ZES [28.2%; χ2= 7.661] group with significant P Value =0.002.The 2-year incidence of ST in the EES group [1.3%] was similar to that in the ZES-S group [2.2%], whereas it was lower in contrast with BMS [7.5%] groups, with significant P value= 0.004]. Conclusion: DES have more efficacy and safety than BMS as EES have lowest MACE and ST rate while BMS have the highest rate and ZES have intermediate rate while the three stent groups have similar rate of mortality at 2 years follow up.